Journal of language and literature - Universitas Sanata Dharma. Department of English Letters (English Letters Department, Universitas Sanata Dharma, 2014)
Linguistics, literature, translation, and cultural studies.
Keywords: English language : Periodicals; English language : Study and teaching : Periodicals; English literature : Periodicals; English literature; English language : Study and teaching; English language